2020
DOI: 10.17583/rimcis.2020.5277
|View full text |Cite
|
Sign up to set email alerts
|

Malaysian Sandwich Generation Issues and Challenges in Elderly Parents Care

Abstract: Ageing is a growing concern all around the world. It is the biggest challenge for developing and developed countries, including Malaysia. Malaysia is a country, where ageing care centre runs under the government, NGOs and public sector, and recently few of the religious centres and entrepreneurs are working in this regard. However, still the facilities are lacking ; therefore; all across Malaysia Sandwich Generation families are still providing support to the elderly by themselves. Hence, this paper aims to hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 33 publications
(48 reference statements)
0
12
0
5
Order By: Relevance
“…A cross-sectional survey conducted on adults aged 35 and older in community pharmacies in the UK, found that women were more likely to have obtained medicines and asked for advice (76 %) than men [ 16 ]. In Malaysia, women are the primary caretakers of children and elders [ 42 ] and are often the ones who visit the pharmacies and assume responsibilities for health in the household where they encourage family members to visit a healthcare professional and ensure family members take medicines and understand treatment [ 43 ]. Pharmacists, as the most accessible health care professionals, are in an ideal position to empower women by supporting and promoting women’s education and by providing them with the information they need to ensure medicines are used responsibly [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional survey conducted on adults aged 35 and older in community pharmacies in the UK, found that women were more likely to have obtained medicines and asked for advice (76 %) than men [ 16 ]. In Malaysia, women are the primary caretakers of children and elders [ 42 ] and are often the ones who visit the pharmacies and assume responsibilities for health in the household where they encourage family members to visit a healthcare professional and ensure family members take medicines and understand treatment [ 43 ]. Pharmacists, as the most accessible health care professionals, are in an ideal position to empower women by supporting and promoting women’s education and by providing them with the information they need to ensure medicines are used responsibly [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The imbalance between work and family is also one of the important stressors to reduce individual career happiness (Bellavia and Frone, 2005). Home-based teachers have to take care of children, deal with the relationships between husbands or wives, as well as the relationships with the elders (e.g., parents-inlaw) in the extended family (Baba, 2018;Noor and Isa, 2020;Park and Park, 2019). All these aspects will consume the individual's psychological capital, thus leading to the reduction of work and life satisfaction.…”
Section: The Mediation Role Of Psychological Capitalmentioning
confidence: 99%
“…Furthermore, adults within 30–45 years have been labelled as the sandwich generation, having to also include elderly care into their duties. Adhering to the responsibility of providing care for both children and the elderly, as emphasized by Malay culture, can increase stress among caregivers [ 37 ]. This could explain why screens become a relief in childrearing among the Malays.…”
Section: Discussionmentioning
confidence: 99%